Al-Quran Verse Imitation Approach in The Construction of Arabic Sentence Pattern - Binti Zakaria, Norfazirah; Mustafa, Nik Farhan; bin Othman, Mohd Sukki (International Journal of Academic Research in Progressive Education and Development, 2021)
The studies on Arabic writing skills in Malaysia are very extensive and dynamic. Although various dimensions have been studied and explored, students’ lack of skills in constructing Arabic sentence pattern remains a major issue. In this matter, an effective and deliberate approach to learning Arabic will help students to overcome this issue. Hence, this study focuses on an Arabic learning method; an imitation approach; which is a part of the features in the Social Learning Theory (Bandura, 1963), in helping students to construct a sentence pattern using the students’ existing knowledge, the Quranic verses. Therefore, this study was conducted in order to identify the students’ ability in constructing the nominal sentence and the verbal sentence through the imitation of Quranic verses and to examine the aspects of mistakes that often take place in the Quranic verses imitation. A total of nine (9) respondents from Form Four students were directly involved in this study. This study which applied a qualitative approach had collected data through questionnaire and a series of interviews. The result shows that the respondents found it easier to build nominal sentence patterns compared to verbal sentence patterns. The respondents that were able to build good Arabic sentence pattern were those who excelled in the Quranic verses memorisation. Other than that, this study also records four (4) types of mistakes that frequently occurred in the imitation process of Quranic verses such as spelling errors, unnecessary addition of ‘ال’ in certain words, incorrect use of madd letter as well as inaccurate use of verbs. Thus, it is hoped that this study will help educators to improve the quality of teaching besides providing them with other possible method in facilitating students to enhance the mastery of writing skills, especially in the construction of (Arabic) sentence pattern.